Twitter profile analysis of the institutions of science and technology in Ibero-America [Análisis de perfiles Twitter de las Instituciones de Ciencia y Tecnología en Iberoamérica] - Coronel Salas, G. (2016)
The rapidity with which information travels on the Internet makes it unquantifiable. To analyze it, it ?s necessary to define the area; so, the dissemination of information on Science and Technology through Twitter is the premise of the investigation. The study seeks to highlight the importance of social networks in the field of science and technology and their influence on the democratization processes. 31 Ibero-America organizations with a profile on microblogging network were analyzed in order to know what type of information they communicate. It was used the technique of Social Network Analysis (SNA) to visualize graphs through each of the connections and communities that these entities have used.